A Comparative Study of Chamomile Oil and Sesame Oil on Chronic Low Back Pain: A Randomized, Double-Blinded, Controlled Clinical Trial - Mina Abolfazli; Seyedeh Fatemeh Jalalinia; Ebrahim Khadem; Hamid Haghani; Shokoh Varaei (Tehran University of Medical Sciences, 2021)
Chronic low back pain (LBP) is common disorder among nurses. The present study compared the effect of rubbing joint oil (chamomile oil product) and sesame oil on the control of chronic LBP in nurses. This study was a double-blind randomized clinical trial conducted on 74 nurses with chronic LBP. The samples were divided into two groups using the randomization method. In the first group, joint oil (chamomile oil product), and in the second group, sesame oil was rubbed twice a day for three weeks. The pain severity was assessed using a visual analog scale before, one, two, three, and four weeks after the intervention. The second outcomes including absenteeism and satisfaction with treatment were also assessed in two groups. Moreover, the mean pain severity decreased, and in both groups, the effect of rubbing both oils was the same after the first week and this effect continued after the fourth week (P < 0.05). There was no statistically significant difference between both groups in terms of absenteeism (P > 0.05) and both groups were satisfied (62/2%) with the effects of oil rubbing. Rubbing joint oil (Chamomile oil product) and Sesame oil is a simple and non-invasive method for controlling LBP. Although the effects of rubbing both oils on pain control were the same, the consequences of low back pain control with rubbing oil were significant.